Comparative Analysis of the Monetary Policies of the Islamic State of Iran and Pakistan - Asep Dadang Hidayat; Yadi Janwari; Sofyan Al-Hakim (al-Afkar, Journal For Islamic Studies, 2024)
This research intends to analyse comparatively the monetary policy in Iran and Pakistan. The object of this research is the Islamic countries of Iran and Pakistan. This research is a descriptive-analytical research with qualitative research, which is a research procedure that produces descriptive data in the form of written words from people and observed behaviour, supported by literature studies. The results of this study indicate that monetary policy in Iran and Pakistan as Islamic countries, both apply Sharia-based monetary, but also opened monetary services to accommodate a number of general, commercial and or conventional economic transactions. This shows that both Iran and Pakistan apply monetary governance that is committed to Islamic law, but is inclusive of conventional ones even though it cannot dominate them.  Monetary governance in both countries plays a more direct role in economic growth, not as an effective moderator of government economic policy.